Medication adherence among chronic obstructive pulmonary disease patients: an interventional study in a tertiary care hospital of Nepal (Nepal Medical College Journal, 2022)
Chronic Obstructive Pulmonary Disease (COPD) is a significant health problem, associated with mortality and morbidities. Low medication adherence is common in patients with COPD. The primary purpose of this study was to evaluate medication adherence after educational intervention was provided to COPD patients. In this interventional study, conducted at a tertiary care center of Nepal from July 2019 to December 2019, a total of 114 patients were divided randomly into two groups: intervention group (patients who received an educational intervention) and control group (patients who received no educational intervention) by using simple randomization technique. The outcomes of educational intervention are then compared between the intervention group and the control group with the aid of the leaflet. A structured questionnaire and the pre-validated Self-Administered Medication Adherence Questionnaire were used to collect information like demographic details and medication adherence. Data were entered and analyzed using SPSS-20 program. Out of 114 patients, only 93 patients came for follow-up after one month. There was a significant improvement in the medication adherence scale score in the intervention group compared to the control group (p